Theranostics in Renal Cell Carcinoma—A Step Towards New Opportunities or a Dead End—A Systematic Review - Katarzyna Jóźwik-Plebanek; Marek Saracyn; Maciej Kołodziej; Olga Kamińska; Adam Daniel Durma; Weronika Mądra; Katarzyna Agnieszka Gniadek-Olejniczak; Marek Dedecjus; Jakub Kucharz; Rafał Stec; Grzegorz Kamiński (Pharmaceuticals)
Background: Renal cell carcinoma is one of the most aggressive urogenital malignancies, with an increasing number of cases worldwide. The majority of cases are diagnosed at an advanced stage, as this form of growth is typically silent. An accurate evaluation of the extent of the disease is crucial for selecting the most appropriate treatment approach. Nuclear medicine imaging is increasingly being applied in oncological diagnostics, prompting ongoing research into renal cell carcinoma markers that could serve as a foundation for theranostic approaches in this disease. Positron emission tomography/computed tomography imaging with prostate-specific membrane antigen (PSMA) ligands has already demonstrated successful utility in diagnosis of other cancers, including prostate cancer and gliomas. Emerging evidence of high sensitivity and specificity in detecting renal cell carcinoma lesions provides a suitable foundation for its application in both the diagnosis and subsequent management of this malignancy. Methods: This systematic review synthesizes the current scientific evidence on the molecular imaging of renal cell carcinoma using PSMA ligands, emphasizing the potential future applications of this imaging marker in theranostic approaches. Results and Conclusions: Based on a systematic review of the literature, it appears that PET/CT with PSMA ligands has the potential to surpass traditional imaging techniques in diagnostic accuracy while also providing valuable prognostic information.